Elastic magnetic curves of ferromagnetic and superparamagnetic models on the surface - Korpinar, Talat; Demirkol, Ridvan Cem; Asil, Vedat (World Scientific Publ Co Pte Ltd, 2021)
We are interested in defining new energy functionals and solving them by using the variational approach method and Darboux equations. That is, we aim to define a new class of elastic curves on the regular surface ?. We further improve an alternative method to find critical points of the bending energy functionals acting on a class of magnetic curves on A. As a result, we classify these critical curves as elastic magnetic curves of the Darboux vector family.
Keywords: Bending energy functionals; Darboux equations; elastic curves; magnetic curves; ferromagnetism; superparamagnetism